The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/cav.121
|View full text |Cite
|
Sign up to set email alerts
|

Bringing haptics and physical simulation together: haptic travel through physical worlds

Abstract: This paper describes our efforts in bringing haptics closer to current dynamic virtual environments (VE). These interactive 3D worlds make more and more use of physical simulations in order to increase realism. As a first step in closing the gap, we propose haptic travel that allows users to feel how their virtual representation navigates through the simulated world. In this work, we show how we coupled stable haptic rendering to physical simulation in order to achieve this. By generating a force feedback fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The overall loop latency for the game showed that the complex computations and rendering in the target shooting game can be simulated at real-time rates that are significantly higher than the minimum update rates of 20-25 Hz for closed-loop virtual training with visual feedback (Jorissen, Boeck, & Lamotte, 2006;Nichols, 1999). These update rates leave a large block of time for other application-specific processes such as the acquisition and processing of the neural command data.…”
Section: Discussionmentioning
confidence: 98%
“…The overall loop latency for the game showed that the complex computations and rendering in the target shooting game can be simulated at real-time rates that are significantly higher than the minimum update rates of 20-25 Hz for closed-loop virtual training with visual feedback (Jorissen, Boeck, & Lamotte, 2006;Nichols, 1999). These update rates leave a large block of time for other application-specific processes such as the acquisition and processing of the neural command data.…”
Section: Discussionmentioning
confidence: 98%